2021
DOI: 10.30699/ajnmc.29.4.302
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Experiences of Palliative Care in the Neonatal Intensive Care Unit: A Qualitative Study

Abstract: Introduction:Palliative care for newborns and their families is urgent. Nurses' experiences need to be considered in order to implement palliative care. Therefore, the present study was conducted to explain the Nurses' Experiences of Palliative Care in the NICU.Methods: This study was conducted by qualitative content analysis in the neonatal intensive care units of Isfahan, Iran, in 2020. Inclusion criteria for nurses were the consent to participate in the study and experience of caring for the newborn and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Furthermore, extracts and subfractions obtained from liquid–liquid extraction, along with selected isolated compounds, were examined for their activity on HaCaT cells in inflammatory conditions, by investigating their activity on IL-6 and TNF-α release and nitrotyrosine formation, along with their effect on claudin-1 and occludin expression. It may be concluded that the aerial parts of R. persica are a rich source of labdane-type diterpenoids with anti-inflammatory and potential wound-healing activity in keratinocytes, thus supporting the traditional application of this plant for the treatment of inflammation and wounds. , …”
Section: Results and Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Furthermore, extracts and subfractions obtained from liquid–liquid extraction, along with selected isolated compounds, were examined for their activity on HaCaT cells in inflammatory conditions, by investigating their activity on IL-6 and TNF-α release and nitrotyrosine formation, along with their effect on claudin-1 and occludin expression. It may be concluded that the aerial parts of R. persica are a rich source of labdane-type diterpenoids with anti-inflammatory and potential wound-healing activity in keratinocytes, thus supporting the traditional application of this plant for the treatment of inflammation and wounds. , …”
Section: Results and Discussionmentioning
confidence: 76%
“…It may be concluded that the aerial parts of R. persica are a rich source of labdane-type diterpenoids with anti-inflammatory and potential woundhealing activity in keratinocytes, thus supporting the traditional application of this plant for the treatment of inflammation and wounds. 14,15 ■ EXPERIMENTAL SECTION General Experimental Procedures. Optical rotations were measured using a JASCO P-2000 polarimeter (Easton, MD, USA).…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been well documented that caring for brain-dead organ donors can be ethically and morally distressing to bedside staff, both in the OR and the ICU. This is related to complex emotional and moral responses to the concept of brain death, the challenges of working with and supporting grieving families, and the need to balance maintaining the dignity of the donor with the requirements of optimizing organs for recovery 7, 9-12…”
Section: A Learning Gapmentioning
confidence: 99%